The initial row in Farsi Poetry - Majid Mansouri; Tahereh Ghasemi (مطالعات زبانی و بلاغی)
The opening line should be seen as a kind of repetition that is abundant in the poetry of traditional and contemporary poets. This kind of repetition, which occurs at the beginning of the verses of the poem, is seen in the poetry of traditional poets, from the same primitive poets as Manouchehri, NaserKhosrow and other poets. However, in the poetry of some poets, such as Sanai, Khaghani, and Shams Moulana's lyric poems, it is more common. In the poetry of contemporary poets, who lack the usual weight, rhyme, and row, these lines are more common. In the poetry of poets such as ForoughFarrokhzad and Ahmad Shamloo, these lines have a higher frequency than poets such as NimaYoshij, Mehdi Akhavan Sales, SohrabSepehri. There are initial lines in different forms and it can be found at the level of syllables, words, sentences and quasi-sentences in the poetry of contemporary and traditional poets. The main purpose of the opening line should be considered its musical aspect. In addition, it is sometimes repeated for other purposes in poetry, such as highlighting, emphasizing the poets in order to convey specific meanings to the audience, and creating coherence in the composition and content of the poem. Sometimes the first line is interpretive and is used as a tool to explain, further explain and clarify the poet's intent, as if the poet intends to explain and convey something to the audience that achieves this goal by repeating a word or phrase. . Other goals and objectives can be seen in these lines. This article seeks to comprehensively address the initial lines in the poetry of prominent traditional poets and modern Persian poets.